Effect of the drainage of cerebrospinal fluid in patients with aneurismal subarachnoid hemorrhage: A meta-analysis. Issue 41 (October 2016) - Qian, Cong; Yu, Xiaobo; Chen, Jingyin; Gu, Chi; Wang, Lin; Chen, Gao; Dai, Yuying
Abstract: Background and objectives: Vasospasm-related injury such as delayed ischemic neurological defect (DIND) or cerebral infarction is an important prognostic factor for aneurismal subarachnoid hemorrhage (SAH). Whether cerebrospinal fluid (CSF) drainage can achieve a better outcome in aneurismal SAH patients after coiling or clipping remains the subject of debate. Here, we report a meta-analysis of the related available literature to assess the effect of continuous CSF drainage on clinical outcomes in patients with aneurismal SAH. Methods: Case-control studies regarding the association between aneurismal SAH and CSF drainage were systematically identified through online databases (PubMed, Web of Science, Elsevier Science Direct, and Springer Link). Inclusion and exclusion criteria were defined for the eligible studies. The fixed-effects model was performed when homogeneity was indicated. Alternatively, the random-effects model was utilized. Results: This meta-analysis included 11 studies. Continuous CSF drainage obviously improved patients' long-term outcome (odds ratio [OR] of 2.86, 95% confidence interval [CI], 1.37–5.98, P < 0.01). CSF drainage also reduced angiographic vasospasm (OR of 0.35, 95% CI, 0.23–0.51, P < 0.01), symptomatic vasospasm (OR of 0.32, 95% CI, 0.32–0.43, P < 0.01), and DIND (OR of 0.48, 95% CI, 0.25–0.91, P = 0.03), but there was no significant difference between the CSF drainage group and the no CSF drainage group on shunt-dependent hydrocephalus (SDHC) prevention (OR of 1.04, 95% CI, 0.52–2.07, P = 0.91). Further analysis on lumbar drainage (LD) and external ventricular drainage (EVD) indicated that LD had a better outcome (OR of 3.11, 95% CI, 1.18–8.23, P = 0.02), whereas no significant difference in vasospasm-related injury was detected between the groups (OR of 1.13, 95% CI, 0.54–2.37, P = 0.75). Conclusion: Continuous CSF drainage is an effective treatment for aneurismal SAH patients; lumbar drainage showed lower complications, but more well-designed studies are required to verify and consolidate this conclusion.